Numerical analysis of the V-Y shaped advancement flap. Issue 10 (October 2015) - Remache, D.; Chambert, J.; Pauchot, J.; Jacquet, E.
Highlights We propose a finite element analysis of the V-Y advancement flap. The key roles of elasticity and natural tension of the skin have been analysed. Minimizing the closure force at the flap apex differs from the shortest gap. The optimal choice of the corner stitch is consistent with the surgeon's technique.